Effects of morphology evolution on solution-processed small molecule photovoltaics via a solvent additive. Issue 31 (24th July 2017) - Hoang, Quoc Viet; Rasool, Shafket; Oh, Sora; Van Vu, Doan; Kim, Da Hun; Lee, Hang Ken; Song, Chang Eun; Lee, Sang Kyu; Lee, Jong-Cheol; Moon, Sang-Jin; Shin, Won Suk
Abstract : A newly synthesized small molecule donor, BDTT-2DPPBFu, is designed for incorporation into the photo-active layer in solution-processed small molecule organic photovoltaics (SM-OPVs). Abstract : A newly synthesized small molecule donor, BDTT-2DPPBFu, is designed for incorporation into the photo-active layer in solution-processed small molecule organic photovoltaics (SM-OPVs). The effects of a solvent additive (1-chloronaphthalene, CN) on the bulk heterojunction morphology of aBDTT-2DPPBFu donor:fullerene derivative acceptor (PC71 BM) are investigated and correlated with the device performance. A TEM analysis revealed that the nanomorphology of the SM-OPVs evolved dramatically with increasing solvent additive volume. With an optimum concentration of 2.5 vol% CN, a nanomorphology with a fibrillar and interpenetrating network on the order of exciton diffusion length (∼10–15 nm) is formed, resulting in improvement of the short-circuit current density, fill factor, and power conversion efficiency. Further GIWAXS studies have shown that the π–π stacking distance ofBDTT-2DPPBFu small molecules is reduced and the inter-mixing of PC71 BM within theBDTT-2DPPBFu -rich phase in the photo-active layer processed from 2.5 vol% CN is increased, leading to enhanced charge transport and reduced charge recombination and transfer resistance. The present work provides important progress in the nanomorphology of the photo-active layer, which can be effectively tuned via the use of a solvent additive in SM-OPVs.